PENGARUH KEPUASAN KERJA DAN PROFESIONALISME TERHADAP KINERJA PEGAWAI KANTOR WALIKOTA BANDAR LAMPUNG - Farah Adila Rahma; Berlintina Permatasari; Ade Candra (Journal of Management Small and Medium Enterprises (SME's))
This research aims to analyze the influence of job satisfaction and professionalism on employee performance in the Bandar Lampung Mayor's Office, especially the Protocol and Leadership Communication section. Job satisfaction reflects an employee's positive attitude towards their work, while professionalism is related to skills and responsibilities in carrying out duties. The study uses a quantitative method with purposive sampling. Data was collected through a questionnaire distributed to 60 respondents. The study results show that job satisfaction and professionalism have a positive and significant effect on employee performance. These findings suggest that organizations need to pay attention to employee job satisfaction and professionalism factors to improve performance.